2019
DOI: 10.3389/fmicb.2019.01083
|View full text |Cite
|
Sign up to set email alerts
|

The Variation of Nasal Microbiota Caused by Low Levels of Gaseous Ammonia Exposure in Growing Pigs

Abstract: Exposure to gaseous ammonia, even at low levels, can be harmful to pigs and human health. However, less is known about the effects of sustained exposure to gaseous ammonia on nasal microbiota colonization in growing pigs. A total of 120 Duroc×Landrace×Yorkshire pigs were housed in 24 separate chambers and continuously exposed to gaseous ammonia at 0,5, 10, 15, 20, and 25 ppm (four groups per exposure level) for 4 weeks. Then, we used high-throughput sequencing to perform 16S rRNA gene analysis in nasal swabs s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 54 publications
3
20
0
Order By: Relevance
“…In vivo testing showed that an increase in ammonia levels, especially above 25 ppm, significantly damaged tracheal mucosa and alveoli, and decreased growth performance [26]. In addition, ammonia levels above 25 ppm reduced the colonization of beneficial bacteria such as Lactobacillus and increased the number of Moraxella and Streptococcus species in the nasal cavities of exposed pigs [26]. Antimicrobial exposure is another key environmental factor that can affect the development of URT microbiome at early stages of life, especially because antimicrobials are widely used for control of post-weaning diarrhoea [28].…”
Section: Initial Colonization and Development Of The Respiratory Tracmentioning
confidence: 99%
See 2 more Smart Citations
“…In vivo testing showed that an increase in ammonia levels, especially above 25 ppm, significantly damaged tracheal mucosa and alveoli, and decreased growth performance [26]. In addition, ammonia levels above 25 ppm reduced the colonization of beneficial bacteria such as Lactobacillus and increased the number of Moraxella and Streptococcus species in the nasal cavities of exposed pigs [26]. Antimicrobial exposure is another key environmental factor that can affect the development of URT microbiome at early stages of life, especially because antimicrobials are widely used for control of post-weaning diarrhoea [28].…”
Section: Initial Colonization and Development Of The Respiratory Tracmentioning
confidence: 99%
“…Ammonia emissions are known for their potential negative consequences on farming environments, the ecosystem, and human and animal health [ 26 ]. The concentration of gaseous ammonia in the farm environment has been shown to affect the porcine airway [ 27 ].…”
Section: Initial Colonization and Development Of The Respiratory Tracmentioning
confidence: 99%
See 1 more Smart Citation
“…In healthy bovine individuals, the URT microbiota (based on nasal and nasopharyngeal swab samples) is dominated by Proteobacteria, a group of bacteria suggested to have high functional variability (Bradley and Pollard, 2017), followed by Tenericutes, Firmicutes and Bacteroidetes (Gaeta et al, 2017;McMullen et al, 2019). Proteobacteria, Firmicutes, and Bacteroidetes are the three most dominant phyla in the URT bacterial communities in piglets (Slifierz et al, 2015;Correa-Fiz et al, 2016;Wang et al, 2019).…”
Section: Host Determinants In a Microbe-dominated World: A Matter Of Speciesmentioning
confidence: 99%
“…In cows and feedlot cattle, several studies have reported how a healthy respiratory microbiota is established in the airways and surveyed which host and environmental factors drive it (Timsit et al, 2016;Hall et al, 2017;Holman et al, 2017;Nicola et al, 2017;Zeineldin et al, 2017a;Holman et al, 2018;Stroebel et al, 2018;Amat et al, 2019;McMullen et al, 2020;Zeineldin et al, 2020a). Analogously, predicting when and how respiratory microbiome breaks down is at the heart of several studies in swine (Cortes et al, 2018;Zeineldin et al, 2018;Jakobsen et al, 2019;Megahed et al, 2019;Mou et al, 2019;Wang et al, 2019;Pirolo et al, 2021). For instance, it appears as though that during weaning, several microorganisms act synergistically to mediate the BRDC (Gaeta et al, 2017;Klima et al, 2019;McMullen et al, 2019;Zeineldin et al, 2019) and PRDC (Wang et al, 2018;Li et al, 2021).…”
Section: Introductionmentioning
confidence: 99%